Electromagnetic Depth Sounding over a Multi-layer Earth - Nimmagadda, Shastri (Scholar Press, 2015)
The present work embodies the results of theoretical investigations on electromagnetic depth sounding using CFS System over a multi-layer earth. Failure of conventional electrical resistivity sounding in the study of geological conditions under resistive overburden calls for variable frequency sounding techniques. Electromagnetic depth sounding which involves the measurement of variation in conductivity with depth may be used for solving various geoengineering and hydrogeological problems associated with stratified earth. Central frequency sounding (CFS) which is one of the depth sounding techniques involving the measurement of vertical component of magnetic field induced at the center of a circular or square loop, is considered in the present study for obtaining theoretical responses over a multi-layer earth. This book contains theoretical foundations and practical ideas (that led to development of commercial ideas for mineral, groundwater/hydro-geological and oil and gas seep investigations). These ideas have been popular in Asia, Australia and even in Europe. This book will be an invaluable contribution for researchers, academicians, mineral and groundwater explorers worldwide.